Principle of good governance in construction of the Jakarta – Bandung fast train project - Constanta, Christine (Trigin Publisher, 2024)
The development of the Jakarta-Bandung High-Speed Rail Project (KCJB) as a national strategic project experienced delays in completion and cost overruns, was considered not urgent and only oriented to the interests of small groups rather than the wider community and brought losses to the state. In making decisions regarding the Jakarta-Bandung High-Speed Rail Project, the government needs to ensure the implementation of the general principles of good governance. The research methodology used is doctrinal research. The implementation of the Jakarta-Bandung High-Speed Rail Project experienced development setbacks and did not fulfill various principles of Good Governance and has a negative impact on aspects of sustainable development. Existing problems range from procurement, planning, development, and evaluation. This means that the principles of participation, transparency, legal certainty, benefit, accuracy, efficiency, effectiveness, accountability, equality, and inclusiveness are not fully applied to the development of the Jakarta-Bandung High-Speed Rail project as a national strategic project.